2014
DOI: 10.1016/j.diagmicrobio.2013.12.007
|View full text |Cite
|
Sign up to set email alerts
|

Phase 3 study comparing tigecycline and ertapenem in patients with diabetic foot infections with and without osteomyelitis

Abstract: A phase 3, randomized, double-blind trial was conducted in subjects with diabetic foot infections without osteomyelitis (primary study) or with osteomyelitis (substudy) to determine the efficacy and safety of parenteral (intravenous [iv]) tigecycline (150 mg once-daily) versus 1 g once-daily iv ertapenem ± vancomycin. Among 944 subjects in the primary study who received ≥1 dose of study drug, >85% had type 2 diabetes; ~90% had Perfusion, Extent, Depth/tissue loss, Infection, and Sensation infection grade 2 or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
110
0
7

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(121 citation statements)
references
References 26 publications
1
110
0
7
Order By: Relevance
“…Studies have indicated that TIG exhibits broad spectrum anti-bacterial ability against Gram-positive and Gram-negative bacteria, including Staphylococcus aureus (Sader et al, 2016), Acinetobacter baumannii (Rao et al, 2016), Enterobacteriaceae (Thaden et al, 2016), among others. As an expanded-spectrum antibiotic, TIG is clinically available for bacterial eradication with a good safety and tolerability profile, particularly for cancer patients (Lauf et al, 2014). Because of intensive myelosuppressive chemotherapy (Razzouk et al, 2006) and surgical site infections, cancer patients are susceptible to infections (Teillant et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Studies have indicated that TIG exhibits broad spectrum anti-bacterial ability against Gram-positive and Gram-negative bacteria, including Staphylococcus aureus (Sader et al, 2016), Acinetobacter baumannii (Rao et al, 2016), Enterobacteriaceae (Thaden et al, 2016), among others. As an expanded-spectrum antibiotic, TIG is clinically available for bacterial eradication with a good safety and tolerability profile, particularly for cancer patients (Lauf et al, 2014). Because of intensive myelosuppressive chemotherapy (Razzouk et al, 2006) and surgical site infections, cancer patients are susceptible to infections (Teillant et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Likewise, a growing body of literature has highlighted the fact that a high minimal inhibitory concentration (MIC) of MRSA strains for vancomycin adversely affects remission in bacteremia 22 or localized osteoarticular infections. 23 These concerns have spurred the development and more widespread use of newer anti-MRSA molecules, such as linezolid, daptomycin, 24,25 tigecycline, 26 ceftaroline, oritavancin, televancin, and dalbavancin. 27 Over the past 15 years, MRSA infection has become a major concern in patients with DFI.…”
mentioning
confidence: 99%
“…Clinical success rates were significantly lower in patients with HAPs and DFIs. This discrepancy is probably due to inclusion of up-to-date published data (16,19,20,24,26) in our meta-analysis, resulting from an updated search of databases. The inferiority of tigecycline may be explained to some extent by the following aspects.…”
Section: Discussionmentioning
confidence: 63%